Commentary: Déjà Vu All Over Again: What’s Wrong With Hart & Risley and a "Linguistic Deficit" Framework in Early Childhood Education? (LEARNing Landscapes, 2013)
In this invited article, the author critiques some of the most often-cited scholarship on children’s early language development and its relationship to children’s learning. She suggests that Hart and Risley’s work, Meaningful Differences, adopts an implicit deficit perspective, and makes unwarranted claims about the impact of children’s early language on their later thinking and learning abilities. In contrast, she proposes an alternative framework that validates the rich and generative language capacities that children bring with them to school (including poor children, dual-language learners, ethnolinguistic minority children, and children who struggle in school). She argues that using "vocabulary size" or "language deficits" as an explanation for school failure locates school failure in children (with no credible basis) rather than in schools as places where children are failing to, but can, under the right circumstances, learn extraordinarily well.
Keywords: early language development; early childhood; learning; language deficit; school failure; learning ability